2015
DOI: 10.1371/journal.pone.0138179
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Use of Antibiotics and Its Associated Factors among Urban and Rural Communities of Bahir Dar City Administration, Northwest Ethiopia

Abstract: BackgroundInappropriate use of antibiotics in the community plays a role in the emergence and spread of bacteria resistant to antibiotics which threatens human health significantly. The present study was designed to determine inappropriate use of antibiotics and its associated factors among urban and rural communities of Bahir Dar city administration.MethodsA comparative cross sectional study design was conducted in urban and rural kebeles of Bahir Dar city administration from February 1 to March 28, 2014. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
132
7
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 49 publications
21
132
7
5
Order By: Relevance
“…The percentage of encounters with antibiotics prescribed was found to be 50.67% which is too much higher than the upper limit of WHO standard, 30% (ideal range, 20-26.8%) [10]. Values that are lower than this finding and closer to the WHO standard were reported from different areas of the globe including 30.3% and 31.8% in Indian healthcare settings [22,30], 29.14% and 31.8% in GUTRH and Bahir Dar, respectively, Ethiopia [19,31]. However, several reports indicated that the prevalence of prescriptions containing antibiotics is even more than this finding.…”
Section: Discussionmentioning
confidence: 92%
“…The percentage of encounters with antibiotics prescribed was found to be 50.67% which is too much higher than the upper limit of WHO standard, 30% (ideal range, 20-26.8%) [10]. Values that are lower than this finding and closer to the WHO standard were reported from different areas of the globe including 30.3% and 31.8% in Indian healthcare settings [22,30], 29.14% and 31.8% in GUTRH and Bahir Dar, respectively, Ethiopia [19,31]. However, several reports indicated that the prevalence of prescriptions containing antibiotics is even more than this finding.…”
Section: Discussionmentioning
confidence: 92%
“…Another factors for misuse and abuse of antibiotics are illiteracy, ignorance and poverty among the people of resource poor countries. [1][2][3] Development of antibiotic resistance is an alarming issue due to inappropriate use of antibiotics and it is a serious challenge to the healthcare professionals. [4] At healthcare professional level, the most common problems with antibiotic therapy are their proper selection, dose and duration.…”
Section: Introductionmentioning
confidence: 99%
“…Helminth infestation may also result in inappropriate antimicrobial use, including antibiotics, perhaps leading to secondary colonization with drug-resistant commensals. The decreased risk associated with school attendance has been observed in a previous study in Spain(17), and may represent a proxy marker for increased socio-economic status, and parental levels of education, which were not evaluated here, but may translate into better awareness of appropriate antibiotic use(18, 19). The decreased risk associated with male gender is unexplained; but independent associations for ESBL-EC/KP colonization have been described for both genders in previous studies(15, 20, 21).…”
Section: Discussionmentioning
confidence: 80%